Low Leakage Current by Solution Processed PTAA-ZnO Transparent Hybrid Hetero-Junction Device - Bablu K. Ghosh; Abdul I. A. Rani; Khairul A. Mohamad; Ismail Saad (2020)
In this work solution processed novel poly-triarylamine (PTAA) organic p-type active layer on inorganic n-ZnO device transparency and electrical properties are investigated under illumination. Low cost organic-inorganic transparent hybrid hetero-junction (HHJ) is a promising candidate for next-generation photovoltaic applications. Greater band gap organic material window layer while inorganic material’s higher thermal stability as HHJ is suitable for detection and photovoltaic applications. However, hetero-interface defects associated leakage current is the key issue of undermining large-area device electrical performance. Hetero-interface defect associated carriers optical absorption limits transparency whereas leakage current density is reliant on physical property and band barrier effect. It is demanded to investigate hetero-device physical stuff and band barrier effect on electrical properties. Novel PTAA is deposited on RF-sputtered inorganic n-ZnO/ITO/glass substrate by spin-coating method. 100 and 60 nm PTAA thin films are deposited with 1,000 and 2,000 revolution per minute (rpm) growth sequence, respectively. PTAA as a transparent p-emitter is shown to absorb incident light beyond visible band, thereby it has promoted excitonic effect. Device I−V characterization carried out at different annealing temperatures and applied voltage. Suitable annealing condition leakage current is shown to reduce nearly 10-4A/cm2 and at higher applied field the greater rectifying I(+)/I(-) ratio is realized. Grain size is shown to increase with annealing effect however; leakage current is remained almost independent of grain size.